Speech masking release in Hybrid cochlear implant users: Roles of spectral and temporal cues in electric-acoustic hearinga) - Tejani, Viral D. (J Acoust Soc Am, 2020)
When compared with cochlear implant (CI) users utilizing electric-only (E-Only) stimulation, CI users utilizing electric-acoustic stimulation (EAS) in the implanted ear show improved speech recognition in modulated noise relative to steady-state noise (i.e., speech masking release). It has been hypothesized, but not shown, that masking release is attributed to spectral resolution and temporal fine structure (TFS) provided by acoustic hearing. To address this question, speech masking release, spectral ripple density discrimination thresholds, and fundamental frequency difference limens (f(0)DLs) were evaluated in the acoustic-only (A-Only), E-Only, and EAS listening modes in EAS CI users. The spectral ripple and f(0)DL tasks are thought to reflect access to spectral and TFS cues, which could impact speech masking release. Performance in all three measures was poorest when EAS CI users were tested using the E-Only listening mode, with significant improvements in A-Only and EAS listening modes. f(0)DLs, but not spectral ripple density discrimination thresholds, significantly correlated with speech masking release when assessed in the EAS listening mode. Additionally, speech masking release correlated with AzBio sentence recognition in noise. The correlation between speech masking release and f(0)DLs likely indicates that TFS cues provided by residual hearing were used to obtain speech masking release, which aided sentence recognition in noise.